Method for preparing mullite whisker adsorption material through co-sintering
The mullite whisker adsorption material prepared by cosintering solves the problems of insufficient acid and alkali resistance and uneven whisker growth of existing materials in alkaline environments, and achieves efficient adsorption of organic matter in printing and dyeing wastewater and good high-temperature desorption cycle performance.
Patent Information
- Application Number
- CN202411804093.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
AI Technical Summary
The existing adsorbent materials have poor acid and alkali resistance, and it is difficult to effectively treat highly alkaline printing and dyeing wastewater. The traditional preparation methods lead to uneven whisker growth, affecting the adsorption performance.
SiO2 and Al(OH)3 are used as raw materials and MoO3 and NH4F are used as a sintering agents to prepare mullite whisker adsorption materials through a one-step co-sintering method, and the amount of additives and sintering conditions are regulated to optimize the morphology and dispersion of whiskers.
The prepared mullite whisker material has excellent chemical stability, thermal stability and high adsorption ability, can effectively adsorb organic matter in printing and dyeing wastewater, and exhibits good desorption cycle performance at high temperatures.
Smart Images

Figure CN119588302A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a mullite whisker adsorption material by co-sintering and application of the method in water treatment. Background Art
[0002] With the development of industrial civilization, the history of human mass production has reached its peak, and with it comes the overload of environmental regulation caused by mass production. Wastewater produced by large-scale industries has also become a key obstacle to restricting environmental protection. According to statistics, with the development of industry, there are currently more than 100,000 commercial dyes, with a rough estimate of 7105-1106 tons per year, and 10-15% of used dyes enter the environment as waste. Dye pollution in the water environment is a major threat to the ecological environment and human health. In addition, they are often multi-colored in water, which will interfere with the transmission of light and affect the metabolism of underwater organisms, causing the ecosystem to be destroyed. Traditional methods for treating wastewater generally use sedimentation and chemical coagulation methods. These two methods can only remove suspended particles, and the removal effect on soluble pollutants, microorganisms and toxic chemicals is not obvious. In addition, the large amount of sludge generated during the chemical coagulation process may also cause secondary pollution. The adsorption method is simple to operate, usually does not require complex equipment and conditions, and is easy to control. At the same time, it has a wide range of applicability, not only for water treatment, but also widely used in air purification, industrial waste gas treatment and solvent recovery.
[0003] Common adsorption materials include carbon materials, COF and MOF. However, the above materials have poor acid and alkali resistance. Printing and dyeing wastewater is often accompanied by a strong alkaline environment. Strong alkali will not only destroy its crystal structure and cause damage to the surface pore structure, but also react with other chemical components, thereby reducing its adsorption activity. Mullite (3Al 2 O 3 ·2SiO 2 ) is a ceramic material with high fire resistance and strong chemical stability. Its main advantages include high temperature stability, good mechanical properties, excellent acid and alkali resistance and chemical stability. In addition, due to its needle-like structure, high aspect ratio and highly developed three-dimensional network structure, it can adsorb small molecular organic matter in sewage and has great potential in the field of water treatment.
[0004] Using MoO 3 As a sintering aid, MoO 3 The low melting point forms a local liquid phase on the particle surface, reducing the melting of SiO 2 The viscosity of Al 3+ From Al 2 O 3 To SiO 2The diffusion rate of MoO is the traditional preparation method for preparing mullite whiskers. By introducing sintering aids, the overall reaction temperature is reduced and the reaction rate is accelerated. 3 Low volatility and uneven distribution in the system will lead to poor uniformity of whisker growth and easy agglomeration between whiskers, which is not conducive to adsorption. 4 F is a common chemical raw material, which is cheap and easy to obtain. The gas phase products generated by its decomposition are evenly distributed, and the presence of HF can effectively regulate the surface energy of the crystal, which is conducive to the uniform growth of whiskers. 3 As a sintering aid, NH 4 F, NH 4 F can react with raw materials to produce gaseous intermediates, which can cause the volatilization and recombination of the substances and further transfer mass in the sintering system, thus providing a continuous raw material supply for the whiskers. 4 The effect of F is relatively strong, which may lead to the excessive growth of mullite whiskers, making it difficult to achieve precise morphology control. 3 and NH 4 The addition content of F and the optimal sintering aid composition and content are preferred, which is helpful to control the formation of mullite whiskers with good morphology and dispersion. Summary of the invention
[0005] The object of the present invention is to provide a mullite whisker adsorption material and a preparation method thereof, aiming to improve the treatment capacity of printing and dyeing wastewater by giving full play to the excellent high-temperature stability, good mechanical properties, excellent acid and alkali resistance, chemical stability, and highly developed three-dimensional network structure of mullite whiskers.
[0006] The product of the present invention adopts SiO 2 、Al(OH) 3 As raw material, MoO 3 and NH 4 F is a sintering aid, and a series of mullite whisker adsorption materials are prepared by a one-step co-sintering method.
[0007] A method for preparing a mullite whisker adsorption material by co-sintering is completed by the following steps and conditions: (1) According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add NH 4 F and MoO 3 ; (2) adding deionized water in a ratio of material: ball: water = 1:1:4, then placing the mixed slurry into a planetary ball mill for ball milling, and then vacuum freeze-drying to obtain a solid powder; (3) Place the sample in a high-temperature tube furnace, heat it to 300 °C at 5 °C / min, keep it at that temperature for 1 h, then heat it to 1100-1400 °C at 10 °C / min, keep it at that temperature, and then cool it to room temperature; (4) After sintering, the mullite whisker sample was sieved to obtain the mullite whisker solid powder, which was thoroughly washed in deionized water and dried in an oven at 60 °C for 12 h. (5) Adjust the temperature, holding time, and NH 4 F and MoO 3 The amount of addition; In step (1), NH 4 The amount of F added is 10-20%; In the step (1), MoO 3 The addition amount is 2-8%; The temperature in step (3) is in the range of 1200 to 1400°C; The insulation time in step (3) is 120 to 210 minutes.
[0008] A formation principle of co-sintering to prepare mullite whisker adsorption material: We propose to use MoO 3 -NH 4 F co-sintering system to prepare mullite whiskers. In the system, MoO 3 During the sintering process, it will react with γ-Al 2 O 3 Solid-solid reaction occurs to form Al 2 (MoO 4 ) 3 The decomposition produces Al with finer grain size and high reactivity. 2 O 3 In addition, the low melting point MoO 3 Reduces the molten SiO 2 The viscosity of Al 3+ diffusion and SiO 2 At the same time, NH 4 The addition of F can be combined with γ-Al 2 O 3 and SiO 2 Reaction to generate gaseous AlOF and SiF 4 This promotes more uniform dislocation growth of the crystals and forms a whisker structure with good dispersion.
[0009] The invention adopts a one-step co-sintering method, has low preparation cost and simple preparation process. Mullite whiskers have excellent chemical stability, thermal stability, aspect ratio and specific surface area. They can adsorb organic matter in printing and dyeing wastewater. In addition, thanks to the excellent thermal stability, mullite whiskers can be desorbed and circulated at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Attached Figure 1 3 is a SEM image of the mullite whisker adsorption material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the present invention is further described below with reference to the accompanying drawings.
[0012] Attached Figure 1 This is a SEM image of mullite whiskers. The existence of the whisker structure can be clearly seen through the SEM image, which can effectively prove that the mullite whiskers have been effectively prepared.
[0013] 2. Experimental process: Weigh 0.2 g of the prepared mullite whisker and place it in a volumetric flask with a methylene blue (MB) solution at a pH of 11 and a concentration of 50 mg / L. Shake it thoroughly to reach adsorption equilibrium, and centrifuge to obtain the supernatant. Measure the concentration of the adsorbed solution using a UV-visible spectrophotometer to calculate the adsorption rate and adsorption amount.
[0014] Example 1 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add 15% NH 4 F and 5% MoO 3 . Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1300 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 93.5% and an adsorption amount of 11.7 mg / g.
[0015] Example 2 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3Add to the ball mill and add 20% NH 4 F and 5%MoO 3 . Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1300 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 91.2% and an adsorption amount of 11.4 mg / g.
[0016] Example 3 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add 10% NH 4 F and 5%MoO 3 . Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1300 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 81.6% and an adsorption amount of 10.2 mg / g.
[0017] Example 4 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add 15% NH 4 F and 2%MoO 3. Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1300 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 71.6% and an adsorption amount of 8.9 mg / g.
[0018] Example 5 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add 15% NH 4 F and 8%MoO 3 . Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 ℃ at 5 ℃ / min, kept warm for 1 h, and then heated to 1300 ℃ at 10 ℃ / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 ℃ for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 76.0% and an adsorption amount of 9.5 mg / g.
[0019] Example 6 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add 15% NH 4 F and 5%MoO 3 . Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1200 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 87.2% and an adsorption amount of 10.9 mg / g.
[0020] Example 7 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add 15% NH 4 F and 5%MoO 3 . Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1400 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 89.6% and an adsorption amount of 11.2 mg / g.
[0021] Example 8 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add 15% NH 4 F and 5%MoO 3 . Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1300 °C at 10 °C / min, kept warm for 120 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 83.2% and an adsorption amount of 10.4 mg / g.
[0022] Example 9 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill and add 15% NH 4 F and 5%MoO 3. Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1300 °C at 10 °C / min, kept warm for 210 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 91.6% and an adsorption amount of 11.5 mg / g.
[0023] Comparative Example 1 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill. Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1300 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, and the adsorption rate was 19.54% and the adsorption amount was 2.44 mg / g.
[0024] Comparative Example 2 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3 Add to the ball mill, and add 5% MoO 3 . Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1400 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 39.52% and an adsorption amount of 4.94 mg / g.
[0025] Comparative Example 3 According to the silicon-aluminum ratio of 2:3, weigh SiO 2 、Al(OH) 3Add to the ball mill and add 15% NH 4 F. Deionized water was added at a ratio of material: ball: water = 1:1:4, and then the mixed slurry was placed in a planetary ball mill for ball milling. After ball milling, solid powder was obtained after vacuum freeze drying. The sample was placed in a high-temperature tube furnace, heated to 300 °C at 5 °C / min, kept warm for 1 h, and then heated to 1300 °C at 10 °C / min, kept warm for 180 min, and then cooled to room temperature. The sintered mullite whisker sample was sieved to obtain a mullite whisker solid powder, which was thoroughly washed in deionized water, taken out and dried in an oven at 60 °C for 12 h. It was placed in a MB solution with a pH of 11 for adsorption, with an adsorption rate of 58.62% and an adsorption amount of 7.33 mg / g.
[0026] in conclusion: at MoO 3 and NH 4 When the F content was 5% and 15% and the sintering temperature was 1300 °C, it had a better effect in the adsorption of alkaline MB solution, and the adsorption rate and adsorption amount were the largest, reaching 93.48% and 11.685 mg / g, respectively.
[0027] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing mullite whisker adsorption material by co-sintering, characterized in that: The main steps are: (1) According to the silicon-aluminum ratio of 2:3, weigh SiO2 and Al(OH)3 and add them into the ball mill, and add a certain amount of NH4F and MoO3; (2) adding deionized water in a ratio of material: ball: water = 1:1:4, then placing the mixed slurry into a planetary ball mill for ball milling, and then vacuum freeze-drying to obtain a solid powder; (3) Place the sample in a high-temperature tube furnace, heat it to 300 °C at 5 °C / min, keep it at that temperature for 1 h, then heat it to a certain temperature at 10 °C / min, keep it at that temperature, and then cool it to room temperature; (4) The sintered mullite whisker sample was sieved to obtain the mullite whisker solid powder, which was thoroughly washed in deionized water and dried in an oven at 60 °C for 12 h.
2. according to the preparation method of the described mullite whisker adsorption material of claim 1, it is characterized in that Mullite whiskers were prepared by one-step sintering method of MoO3-NH4F co-sintering system; In step (1), the amount of NH4F added is 10-20%; In the step (1), the amount of MoO3 added is 2-8%; The temperature in step (3) is in the range of 1200 to 1400°C; The insulation time in step (3) is 120 to 210 minutes.
3. The mullite whisker obtained by the preparation method according to claim 1 is applied to printing and dyeing wastewater and other water treatment directions.